FITUR CLOSE FRIENDS INSTAGRAM SEBAGAI KETERBUKAAN DIRI MAHASISWA YANG MENGALAMI KECEMASAN BERMEDIA SOSIAL - Faridah Azza Annabillah; Kheyene Molekandella Boer (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Instagram Close Friends Feature as Self Disclosure of University Communication Science Students Experiencing Social Media Anxiety. The purpose of this study was to describe the Instagram close friends feature as self-disclosure for Mulawarman University Communication Science students who experience social media anxiety. The type of research used is descriptive qualitative research method. The research focus refers to five aspects of self-disclosure according to Wheeles and Grotz (1976), namely purpose, amount, valence, accuracy and honesty, and depth. The data collection techniques used were observation, interview, and documentation. The stages of data analysis were carried out using the Miles and Huberman model, namely data reduction, data presentation, conclusion drawing and verification. The results showed the purpose of Mulawarman University Communication Science students using close friends as self-disclosure to channel ideas, information, emotions, complaints, outpourings, opinions, hobbies, romantic relationships, entertainment. All informants have anxiety when expressing themselves on social media, especially public Instagram. There is no difference in self-disclosure between men and women. The amount of self-disclosure carried out, in a day they upload a minimum of two posts or more on the close friends feature depending on the mood. The valence of self-disclosure is positive and negative. All informants have carefulness in controlling their self-disclosure, the information disclosed is honest and not exaggerated. They select close friends followers based on peers who are familiar and can be trusted to maintain each other's privacy information.